Identification and characterization of atypical 2-cysteine peroxiredoxins from mud crab Scylla paramamosain: The first evidence of two peroxiredoxin 5 genes in non-primate species and their involvement in immune defense against pathogen infection. Issue 69 (October 2017) - Tu, Dan-Dan; Jiang, Mei; Gu, Wen-Bin; Zhou, Yi-Lian; Zhu, Qi-Hui; Zhou, Zhong-Kai; Chen, Yu-Yin; Shu, Miao-An
Abstract: Peroxiredoxin 5 (Prx5) belongs to a novel family of evolutionarily conserved antioxidant proteins that protect cells against various oxidative stresses. Generally, no more than one Prx5 transcript had been reported in non-primate species. In this study, two Prx5 genes (coined as SpPrx5-1 and SpPrx5-2 ) were firstly isolated from the mud crab, Scylla paramamosain, through RT-PCR and RACE methods. The open reading frame of SpPrx5-1 and SpPrx5-2 were 561 bp and 429 bp in length, encoding 186 and 142 amino acids polypeptide, respectively. Both the conserved signatures of peroxiredoxin catalytic center and Prx5-specific domain were identified in Sp Prx5-1 and Sp Prx5-2. Phylogenetic analysis indicated that both Sp Prx5 clustered together with other animal Prx proteins and were classified into Prx5 subfamily. Tissue-specific expression analysis revealed that both SpPrx5-1 and SpPrx5-2 were ubiquitously expressed, highest in hepatopancreas, and showed remarkably similar transcription patterns. Quantitative RT-PCR analysis exhibited that both SpPrx5 genes changed dramatically in hepatopancreas, although showing different expression profiles, after virus-analog poly (I:C) or Vibrio alginolyticus challenge. The expression levels of both SpPrx5 s were significantly enhanced in hepatopancreas after poly (I:C) stimulation, while SpPrx5-2 exhibited a more prompt response than SpPrx5-1 . Nevertheless, the expression levels of both SpPrx5 s were significantly reduced in hepatopancreas after Vibrio alginolyticus challenge in which SpPrx5-1 showed a more prompt response than SpPrx5-2 . These results suggested the involvement of Sp Prx5s in responses against viral and bacterial infections and further highlighted their functional importance in the immune system of Scylla paramamosain . Highlights: Two Prx5 genes were identified in one species for the first time. The expression profiles of two SpPrx5 genes were different after immune stimuli. Both SpPrx5 genes may be involved in immune defense against pathogen infection.